Non-EFL Students’ Spontaneous Technique to Reduce Anxiety in ELT Speaking Practice Class - Kurniawan, Agung Budi (Universitas PGRI Adi Buana Surabaya, 2023)
This research investigated non-EFL students’ spontaneous technique to reduce their English-speaking anxiety. This research proposes an instrument in three areas and the findings are parallel with them. The first scope is the use of various instruments which could give both strengths and lacks to students. The proper instruments help students to maintain the time necessary. The inappropriate use of the instrument lengthens students’ time to perform their speaking. The second finding scope is students' method of reducing anxiety through managing language use which covers diction, synonym, intonation management, length of speech, punctuation use, and repetition. The verbal language used represents students' previous experience and their readiness. The third finding scope is students’ method of reducing anxiety through managing non-linguistic aspects that cover facial expression, eye contact, body language, and changing of standing up position. The main conclusion is that reducing anxiety needs a well-prepared method or program.